2013
DOI: 10.4103/0973-1482.113380
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative abdominal drainage following major upper gastrointestinal surgery: Single drain versus two drains

Abstract: The insertion of drains did aid in the detection of complications following gastric and pancreatic surgery. Two drains offer no further advantage over one drain in terms of detection of complications. While the number of drains did not contribute to, or reduce, the morbidity and mortality in the two groups, the use of one drain significantly reduced hospital stay. Taken together, these findings support the prophylactic insertion of a single intra-abdominal drain following gastric and pancreatic resections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 19 publications
1
14
1
Order By: Relevance
“…The use of single or multiple drains in pancreatic surgery has failed to show any relevant interest in a single center retrospective study [39]. In the same topic as our study, a chinese randomized trial from Jiang et al has reported a decrease of both grade C POPF rate and length of hospital stay with CSD [40].…”
Section: Discussionmentioning
confidence: 71%
“…The use of single or multiple drains in pancreatic surgery has failed to show any relevant interest in a single center retrospective study [39]. In the same topic as our study, a chinese randomized trial from Jiang et al has reported a decrease of both grade C POPF rate and length of hospital stay with CSD [40].…”
Section: Discussionmentioning
confidence: 71%
“…An encouraging trend towards lesser use of drains is also possible due to the high success rate of image-guided interventions [61]. In one of our studies, we showed that drains help in identifying 62 % of complications after major upper gastrointestinal surgery [62]. The use of two drains did not provide any advantage, rather increased hospital stay, and hence, a single drain was sufficient [62].…”
Section: Role Of Drainsmentioning
confidence: 76%
“…Drains could possibly be avoided in patients with low risk of POPF [46]. However, the majority of pancreatic surgeons still consider routine placement of intraabdominal drains mandatory [15-17]. Once a decision is made to use intraabdominal drains, a controversy remains about which type of drain is most suitable in pancreatic resection [47].…”
Section: Discussionmentioning
confidence: 99%
“…The main significance of the drains is to prevent formation of intraabdominal fluid collection; furthermore, it helps with early diagnosis of postoperative bleeding, pancreatic and biliary leak, or anastomotic dehiscence [15-17]. In some cases, keeping the drain in place for a longer period of time can be part of conservative treatment of the pancreatic fistula, such as by creating a controlled pancreaticocutaneous fistula until the fistula has healed spontaneously without any additional treatment [11,18].…”
Section: Introductionmentioning
confidence: 99%